Rethinking development strategies after the financial crisis. Vol. 1 : Making the case for policy space (United Nations New YorkUS, 2015)
Analyses the need to adjust developing strategies after the global financial crisis in a context of expected future slow growth in the North. Analyses also seven development strategies, viz., the Washington Consensus, neoliberalism, good governance, the UN Millennium Development Goals, export-led growth, industrialisaion and a heterodox macroeconomic strategy for development. Aims to identify the main middle-income traps and presents a critical review of the literature. Discusses the relevance of industrial policy for developing countries, given the rising interest shown in this type of policy by politicians and economists in both the developed and developing world after the 2008 global financial crisis. Argues that it is imperative for countries to have the national-level flexibility to meet global development goals.
Keywords: DEVELOPMENT STRATEGY